The secret of snow [large type] - Shipman, Viola (Center Point Large Print, 2022)
"When Sonny Dunes, a SoCal meteorologist whose job is all sunshine and seventy-two-degree days, is replaced by a virtual meteorologist that will never age, gain weight or renegotiate its contract, the only station willing to give the fifty-year-old another shot is the very place Sonny's been avoiding since the day she left for college -- her northern Michigan hometown. Sonny grudgingly returns to the long, cold, snowy winters of her childhood ... with the added humiliation of moving back in with her mother. Not quite an outsider but no longer a local, Sonny finds her past blindsiding her everywhere: from the high school friends she ghosted, to the former journalism classmate and mortal frenemy who's now her boss, to, most keenly, the death years ago of her younger sister, who loved the snow. To distract herself from the memories she's spent her life trying to outrun, Sonny throws herself headfirst into covering every small-town winter event to woo a new audience, made more bearable by a handsome widower with optimism to spare. But with someone trying to undermine her efforts to rebuild her career, Sonny must make peace with who she used to be and allow her heart to thaw if she's ever going to find a place she can truly call home"--Provided by publisher